THE IMPORTANCE OF BONE MARROW AND CORD BLOOD BANKING IN THE SEARCH OF UNRELATED STEM CELL DONORS - Fatma Savran Oğuz (İstanbul Tıp Fakültesi Dergisi)
In approximately 30% of the patients who planned to undergo allogeneic stem cell transplantation, HLA-matched donors can be found from either siblings or related donors. For the remaining 70%, the source of healthy donor stem cells are provided by bone marrow or cord blood banks generated by the contribution of volunteer donors. Each country registers the HLA phenotype data of their donors into an international database. The World Marrow Donor Association (WMDA) is the world's largest hematopoietic cell database, listing more than 36 million stem cell donors and over 800,000 cord blood units. It serves as a worldwide network that organizes Hematopoietic Stem Cells (HSC) transplantations from unrelated donors for those in need. WMDA consists of 137 hematopoietic cell donor registries from 55 countries, and 53 cord blood banks from 36 countries. The shared network enables clinicians and other healthcare professionals with a role in donor selection to search all the registries simultaneously around the world. More than 49% of all the stem cell products are delivered across international borders in the hands of licensed couriers. The Istanbul Faculty of Medicine Bone Marrow Bank was the first bank established in Turkey. There are three bone marrow banks (Istanbul University Istanbul Faculty of Medicine Bone Marrow Bank, Ankara University Faculty of Medicine Bone Marrow Bank, and TURKOK-established in the Ministry of Health) in Turkey for a national and international search of donors. The Ankara University Unrelated Cord Blood Bank is the only public bank in Turkey, which has an international accreditation certificate ''FACT NETCORD''.